If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 + 2x = -2(-3 + -4x) 30 + 2x = (-3 * -2 + -4x * -2) 30 + 2x = (6 + 8x) Solving 30 + 2x = 6 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 30 + 2x + -8x = 6 + 8x + -8x Combine like terms: 2x + -8x = -6x 30 + -6x = 6 + 8x + -8x Combine like terms: 8x + -8x = 0 30 + -6x = 6 + 0 30 + -6x = 6 Add '-30' to each side of the equation. 30 + -30 + -6x = 6 + -30 Combine like terms: 30 + -30 = 0 0 + -6x = 6 + -30 -6x = 6 + -30 Combine like terms: 6 + -30 = -24 -6x = -24 Divide each side by '-6'. x = 4 Simplifying x = 4
| 2x+75=1x | | 1.07x=192.60 | | x=.6*180 | | -5(3-q)+4= | | 8h+5=61 | | x^2+3x+xy=-3y | | 19-4(y+-2)=5y | | x^2+3x+xy=3y | | (X+2)(x-7)=o | | 3y^2+24y+12=0 | | 2x+x=76 | | 33+15=17w-w+4w | | 23=3(M-1)-1 | | 7m-21=42 | | (6+s)-8=2s-23 | | k*k-8=-7 | | 6x+8x-x=-5x | | -1.6(b-3.35)=-11.28 | | 3(x^2)-2+2Sinx=0 | | 2(m+4)=3(m-1) | | 4x^3+3x^2=7x | | 25(2x+1)3+10(2x+1)2-35(2x+1)= | | 2e^3x=-3 | | 12867=x+.467 | | -6=-4+2s | | P=29+2w | | b+b=-6 | | 4r^3+10r^2-6r=0 | | 9+v=v+6 | | 5y-8-3y+2=10 | | 3(1+8x)=-117 | | 4.20*12= |